Recycling - Blashfield, Jean F.; Black, Wallace B. (Chicago : Childrens Press, 1991)
Discusses the advantages of recycling and what can be done to protect the environment from further damage.
"A production of B&B Publishing"--T.p. verso.
Includes index.
Wilson's Junior High School.
6.1
5-8
Keywords: Environmental protection -- Citizen participation -- Juvenile literature; Recycling (Waste, etc.) -- Juvenile literature; Refuse and refuse disposal -- Juvenile literature; Environmental protection; Recycling (Waste); Refuse and refuse disposal; Environmental protection; Recycling; Refuse and refuse disposal